Co-creation of patient engagement quality guidance for medicines development: an international multistakeholder initiative. Issue 1 (January 2019) - Deane, Katherine; Delbecque, Laure; Gorbenko, Oleksandr; Hamoir, Anne Marie; Hoos, Anton; Nafria, Begonya; Pakarinen, Chi; Sargeant, Ify; Richards, Dawn P; Skovlund, Soren Eik; Brooke, Nicholas
Abstract : Introduction: Meaningful patient engagement (PE) can enhance medicines' development. However, the current PE landscape is fragmentary and lacking comprehensive guidance. Methods: We systematically searched for PE initiatives (SYNaPsE database/publications). Multistakeholder groups integrated these with their own PE expertise to co-create draft PE Quality Guidance which was evaluated by public consultation. Projects exemplifying good PE practice were identified and assessed against PE Quality Criteria to create a Book of Good Practices (BOGP). Results: Seventy-six participants from 51 organisations participated in nine multistakeholder meetings (2016–2018). A shortlist of 20relevant PE initiatives (from 170 screened) were identified. The co-created INVOLVE guidelines provided the main framework for PE Quality Guidance and was enriched with the analysis of the PE initiatives and the PE expertise of stakeholders. Seven key PE Quality Criteria were identified. Public consultation yielded 67 responses from diverse backgrounds. The PE Quality Guidance was agreed to be useful for achieving quality PE in practice, understandable, easy to use, and comprehensive. Overall, eight initiatives from the shortlist and from meeting participants were selected for inclusion in the BOGP based on demonstration of PE Quality Criteria and willingness of initiative owners to collaborate. Discussion: The PE Quality Guidance and BOGP are practical resources which will be continually updated in response to user feedback. They are not prescriptive, but rather based on core principles, which can be applied according to the unique needs of each interaction and initiative. Implementation of the guidance will facilitate improved and systematic PE across the medicines' development lifecycle.